Inherent DNA‐binding specificities of the HIF‐1α and HIF‐2α transcription factors in chromatin. (14th November 2018) - Smythies, James A; Sun, Min; Masson, Norma; Salama, Rafik; Simpson, Peter D; Murray, Elizabeth; Neumann, Viviana; Cockman, Matthew E; Choudhry, Hani; Ratcliffe, Peter J; Mole, David R
Abstract: Hypoxia‐inducible factor (HIF) is the major transcriptional regulator of cellular responses to hypoxia. The two principal HIF‐α isoforms, HIF‐1α and HIF‐2α, are progressively stabilized in response to hypoxia and form heterodimers with HIF‐1β to activate a broad range of transcriptional responses. Here, we report on the pan‐genomic distribution of isoform‐specific HIF binding in response to hypoxia of varying severity and duration, and in response to genetic ablation of each HIF‐α isoform. Our findings reveal that, despite an identical consensus recognition sequence in DNA, each HIF heterodimer loads progressively at a distinct repertoire of cell‐type‐specific sites across the genome, with little evidence of redistribution under any of the conditions examined. Marked biases towards promoter‐proximal binding of HIF‐1 and promoter‐distant binding of HIF‐2 were observed under all conditions and were consistent in multiple cell type. The findings imply that each HIF isoform has an inherent property that determines its binding distribution across the genome, which might be exploited to therapeutically target the specific transcriptional output of each isoform independently. Synopsis: The HIF‐1 and HIF‐2 transcription factors display overlapping but distinct, inherent chromatin binding preferences that are independent of cell‐type, degree or duration of hypoxia, or competition between isoforms. HIF‐α subunits bind in stoichiometric ratio with HIF‐1β. HIF‐1 binds closer to promoters, while HIF‐2 binds distal enhancers and their inherent distributions are unaffected by the degree or duration of hypoxia or the cell type. HIF‐1 and HIF‐2 do not compete for binding sites. Abstract : The HIF‐1 and HIF‐2 transcription factors display overlapping but distinct, inherent chromatin binding preferences that are independent of cell‐type, degree or duration of hypoxia, or competition between isoforms.